2011
DOI: 10.1039/c1dt10368g
|View full text |Cite
|
Sign up to set email alerts
|

Gold(i) complexes of water-soluble diphos-type ligands: Synthesis, anticancer activity, apoptosis and thioredoxin reductase inhibition

Abstract: Gold(I) complexes of imidazole and thiazole-based diphos type ligands were prepared and their potential as chemotherapeutics investigated. Depending on the ligands employed and the reaction conditions complexes [L(AuCl)(2)] and [L(2)Au]X (X = Cl, PF(6)) are obtained. The ligands used are diphosphanes with azoyl substituents R(2)P(CH(2))(2)PR(2) {R = 1-methylimidazol-2-yl (1), 1-methylbenzimidazol-2-yl (4), thiazol-2-yl (5) and benzthiazol-2-yl (6)} as well as the novel ligands RPhP(CH(2))(2)PRPh {R = 1-methyli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…Distribution Coefficient (log D 7.4 ): The n ‐octanol/water coefficients of the complexes were determined as previously reported using the shake‐flask method. Buffered distilled water (100 mL, phosphate buffer [PO 4 3– ] = 10 µ m , [NaCl] = 0.15 m , pH 7.4) and n ‐octanol (100 mL) were shaken together for 72 h to allow saturation of both phases.…”
Section: Methodsmentioning
confidence: 99%
“…Distribution Coefficient (log D 7.4 ): The n ‐octanol/water coefficients of the complexes were determined as previously reported using the shake‐flask method. Buffered distilled water (100 mL, phosphate buffer [PO 4 3– ] = 10 µ m , [NaCl] = 0.15 m , pH 7.4) and n ‐octanol (100 mL) were shaken together for 72 h to allow saturation of both phases.…”
Section: Methodsmentioning
confidence: 99%
“…6 During the early phases of metallodrug research, it was found that derivatives containing the linear P-Au-S structure found in auranofin (a known rheumatoid arthritis drug) had potential for treating cancer. 5 Successful cancer treatments are expected to selectively kill diseased cells only and the cytotoxic effects of the drugs are routinely monitored by conventional biochemical assays such as 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) reduction assays, 7 microscopy, flow cytometric techniques, 8 and real time cell electronic sensing (RT-CES). 9 The disadvantages of some of these techniques are that expensive reagents are needed and specialised instruments to measure absorbance, impedance, fluorescence, or luminescence of labelled biosensors.…”
mentioning
confidence: 99%
“…In the literature, gold complexes have been studied for potential antitumor properties, and it was shown that complexes of the type [(R 3 P)Au(thiolate)] exhibit antitumor properties; furthermore, gold(I) phosphane derivatives or gold(I) complexes of bisphosphanes have also shown significant activity in murine tumor . In addition, although gold(I) complexes like [(dppe) 2 Au] + (dppe = 1,2‐bis‐(diphenylphosphino)ethane) exhibit promising cytotoxicity in preclinical studies, they produce other severe adverse effects (cardiac, hepatic and vascular toxicity) .…”
Section: Introductionmentioning
confidence: 99%